Developing a Model for Machine Building Companies to Be Restructured in Russian Mono Company Towns as a Factor and a Condition of Well-Being; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Shabashev V. A. Vladimir Alekseevich (2016, 2016)
Title screen